2020
DOI: 10.1080/03637751.2020.1809685
|View full text |Cite
|
Sign up to set email alerts
|

The role of information avoidance in managing uncertainty from conflicting recommendations about electronic cigarettes

Abstract: Insufficient scientific evidence about electronic cigarettes (ecigarettes) has led to conflicting recommendations (CRs) by credible scientific organizations, creating a public health debate that could prove especially difficult to reconcile as current and former smokers make decisions about whether to use e-cigarettes. To investigate how CRs about e-cigarettes may affect intentions to engage in healthy behaviors, 717 former and current smokers were randomly exposed to one of five conditions (varying in the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 41 publications
(83 reference statements)
1
9
0
Order By: Relevance
“…Nonetheless, we found that need for closure and people’s initial efficacy beliefs worked in tandem to influence message response: MRMs with a nicotine warning only enhanced efficacy beliefs of smokers with low initial efficacy beliefs and low need for closure. Consistent with a recent study [ 25 ], this suggests the importance of considering individuals’ motivational and cognitive differences in the assessment of mixed communication surrounding e-cigarettes.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Nonetheless, we found that need for closure and people’s initial efficacy beliefs worked in tandem to influence message response: MRMs with a nicotine warning only enhanced efficacy beliefs of smokers with low initial efficacy beliefs and low need for closure. Consistent with a recent study [ 25 ], this suggests the importance of considering individuals’ motivational and cognitive differences in the assessment of mixed communication surrounding e-cigarettes.…”
Section: Discussionsupporting
confidence: 88%
“…In another experiment [ 24 ], 2056 U.S. adults reported no differences between conflicting e-cigarette messages and control messages whereas positive and negative e-cigarette messages produced responses consistent with the messages. Very recently, scholars [ 25 ] found that personal characteristics impacted people’s responses to e-cigarette messages mentioning both positive and negative product effects. Specifically, among those with a low information avoidance tendency, exposure to conflicting e-cigarette information produced more confusion than one-sided anti-e-cigarette messages or control messages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the positive and negative consequences of information avoidance on effective coping behaviors and crisis management, information avoidance has received less attention than other coping strategies such as information seeking ( Brashers et al., 2002 ; Yang et al., 2020 ). The prevalence and predictors of avoidance are not well-understood ( Emanuel et al., 2015 ; Narayan et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%